The relationship between leadership behaviors and shared decision-making - Hanna, Jamal (Beirut Notre Dame University.Humanities, 2014)
The study investigated the relation between the 5 components of leadership behaviors: Model the Way, Inspire a Shared Vision, Challenge the Process, Enable Others to Act, and Encourage the Heart, and the engagement level of 88 teachers in the shared decision-making process at 10 schools (5 public and 5 private) in Lebanon, at the level of planning, policy development, curriculum/instruction, student achievement, pupil personnel services, staff personnel, staff development, and budget management. The Leadership Practices Inventory LPI and Decision-making Questionnaire were used to measure the leadership behavior and teacher s engagement in decision-making respectively. Descriptive and correlation analysis were used to analyze data. The results concluded that the more the leader practices leadership behaviors appropriately, the more engaged teachers would be in the decision-making process at school. The degree of correlation differs between the type of behavior and the area of decision making; some behaviors showed significant and positive correlation with all areas of decision making, while other behaviors had lower correlation degree, or no correlation with specific areas of decision making. In addition, it was found that some demographic variables have an effect on the shared decision-making process. Teaching in a private or a public school can significantly affect the level of teacher s engagement in the decision-making process, while gender, years of experience, and education level showed no significant effect on the level of teacher s engagement in the decision-making process.
: Mémoire
Keywords: Leadership; Leadership